Age model of sediment core PS67/197-1 - Loftfield, Julia; Nowaczyk, Norbert R; Lembke-Jene, Lester; Frederichs, Thomas; Lachner, Johannes; Lamy, Frank; Rugel, Georg; Stübner, Konstanze; Adolphi, Florian
Age model of PS67/197-1 28 – 60 ka BP. Model is based on correlating magnetic susceptibility to δ18O of EDML and paleomagnetic measurements to the Black Sea core stack of Liu et al. (2020). The model is an update of the one of Xiao et al. (2016).